Pengaruh Arus Kas Operasi, Belanja Modal, dan Dividend Payout Ratio terhadap Prediksi Laba pada Perusahaan yang Terdaftar di Indeks LQ 45 Tahun 2011-2015 - Elfindari, Puput (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This purpose of this research is to examine the effect of operating cash flow, capital expenditures, and dividend payout ratio on earnings predictions on companies listed in the LQ 45 2011-2015.Secondary data used were sourced from the financial statements, published by the Indonesia Stock Exchange which is the reference center of the capital market in Indonesia. Type of study used in this study is hypothesis testing by purposive sampling method. There are 65 samples of data which is the object of research. The studys hypotheses were tested using multiple linear regression.The results of this research show that simultaneous of operating cash flow, capital expenditures, and dividend payout ratio have effect on the prediction of future earnings. Partially the research showes that (1) Operating cash flow significantly influence on predictions of future earnings, (2) capital expenditures significantly influence on predictions of future earnings, (3) dividend payout ratio significantly influence on predictions of future earnings.